The era of targeted therapy for hyperlipidemia - U. V. Chubykina; A. V. Tyurina; M. V. Ezhov (Российский кардиологический журнал, 2024)
Despite a variety of lipid-lowering drugs, mostly pelleted, aimed at reducing low-density lipoprotein cholesterol and triglycerides, only a small number of patients achieve their target levels. The reasons are insufficient adherence to treatment, rare use of combined lipid-lowering therapy regimens by attending physicians, low availability and high cost of injected lipid-lowering agents. With the advent of technologies for targeted therapy for hyperlipidemia, a new era in cardiology opens. These innovations will lead to higher goal achievement rates through a personalized and precision approach to hyperlipidemia treatment. Novel lipid-lowering drugs are directed at the molecular targets of hypercholesterolemia, hyperlipoproteinemia(a) and hypertriglyceridemia. The review purpose is to systematize following information about innovative lipid-lowering drugs: mechanism of action, stage of development, effectiveness and safety.